An undergraduate laboratory activity on molecular dynamics simulations. Issue 2 (11th January 2016) - Spitznagel, Benjamin; Pritchett, Paige R.; Messina, Troy C.; Goadrich, Mark; Rodriguez, Juan
Abstract: Vision and Change [AAAS, 2011] outlines a blueprint for modernizing biology education by addressing conceptual understanding of key concepts, such as the relationship between structure and function. The document also highlights skills necessary for student success in 21st century Biology, such as the use of modeling and simulation. Here we describe a laboratory activity that allows students to investigate the dynamic nature of protein structure and function through the use of a modeling technique known as molecular dynamics (MD). The activity takes place over two lab periods that are 3 hr each. The first lab period unpacks the basic approach behind MD simulations, beginning with the kinematic equations that all bioscience students learn in an introductory physics course. During this period students are taught rudimentary programming skills in Python while guided through simple modeling exercises that lead up to the simulation of the motion of a single atom. In the second lab period students extend concepts learned in the first period to develop skills in the use of expert MD software. Here students simulate and analyze changes in protein conformation resulting from temperature change, solvation, and phosphorylation. The article will describe how these activities can be carried out using free software packages, including Abalone and VMD/NAMD. © 2016 by The International Union of Biochemistry and Molecular Biology, 44:130–139, 2016.